Load on back in concrete reinforcement work. - Saari, Jorma; Wickström, Gustav (Scandinavian Journal of Work, Environment & Health, 1978)
The demands of work on the back of concrete reinforcement workers was determined through 4,327 observations of the various work postures and the weights lifted. Static loads from forward-leaning and bent-double postures were found to be common. In the preparation of intermediate and thick rods, forward-leaning was required for more than a third of the total work time, while one central assembly task required work in the bent-double posture for 58% of the total work time. The dynamic loads were of less importance, even though weights over 30 kg were lifted about 15% of the time in the preparation tasks and momentary forces approaching 1,000 N were occasionally needed. The bent-double posture, combined with or quickly followed by additional strain from, for example, weight lifting or slipping, was considered the most probable cause for possible signs of accelerated lumbar disc degeneration, while also the forward-leaning postures could be responsible for reversible low-back symptoms.
Keywords: back; back load; concrete reinforcement work; concrete work; dynamic load; load; static load